ADRENOMEDULLIN2 ANTAGONIST ALTERS FETOPLACENTAL GROWTH RATE DURING RAT LATE GESTATION - G. LAKSHMI DEEPIKA; JOSTHNA PENCHALANENI (International Journal of Pharma and Bio Sciences, 2013)
Adrenomedullin-2 (ADM2), a novel calcitonin/calcitonin-gene related peptide family with an exon-intron structure similar to that of ADM. The aim of the present study is to evaluate the role of Adrenomedullin-2 (ADM2) on fetoplacental development in female pregnant albino rats and to evaluate the effect of adrenomedullin2 antagonist (ADM217-47) on fetal and placental development in late gestation of pregnant rats. The pregnant rats were continuously exposed with Adrenomedullin2 antagonist (ADM217-47) at the concentration of 50 µg and 200 µg / rat / day by inserting osmotic mini pumps from the 18th gestational day onwards and the rats were sacrificed on 22nd gestational day to evaluate the placental and fetal growth. Earlier studies of antagonism of ADM2 function during rat pregnancy caused fetal growth restriction, and also decreased the fetoplacental weight. The histopathological studies ADM2 infusion caused impairment of labyrinths and distortion of deciduas in placenta. In immunohistochemical studies the presence of caspase-3 protein was observed in the uterus and placental tissues, this is confirmed by western blot analysis, the caspase-3 was significantly increased in both uterus and placental tissues were as Bcl-2 was significantly decreased when compared with the controls. Therefore the present study reveals the potential role of ADM2 in regulation of fetoplacental growth during rat late gestation.